Zagrożenia przebiegu procesu wychowania we współczesnej rodzinie polskiej -jakościowa analiza opinii - Kowalczyk-Szymańska, Mirosława (Wydawnictwo Naukowe UAM, 2005)
The article presents the outcome of a poll carried out among 400 families in the city of Bełchatów. Basing on the results, it may be concluded that in the families investigated there are many factors threatening the process o f upbringing. The reasons for this are such features characteristic of social processes as the orientation towards possessions (the “to have” modus), the consumptionist lifestyle, the lack of time, combined with inertia, alienation, negation, authoritarianism, and violence. These cause many negative phenomena in the family which have detrimental influence on the process of upbringing
The threats to the process of upbringing in the contemporary Polish family. A qualitative opinion poll analysis